Potential Occurrence of Decubitus and Phlebitis - Karo, Mestiana Br.; Pane, Jagentar Parlindungan; Marbun, Noventina (Indonesian Journal of Global Health Research, 2024)
Pressure sores (decubitus) are wounds caused by a lack of blood vascularization in the area of the skin that gets the most pressure due to prolonged bed rest, while phlebitis is inflammation of the intima of the veins and is usually associated with pain and tenderness along the cannulated vein, erythema, warmth and scratch formation with the palpable cord. Objective: This study aims to describe the potential for decubitus and phlebitis to occur at Santa Elisabeth Hospital Medan 2023. Method: Descriptive research design using purposive sampling technique with a total of 80 respondents. The research instrument uses the Braden scale assessment form to determine the risk of pressure ulcers and the VIP Score assessment form to determine the risk of phlebitis using observation techniques in data collection. For data analysis, univariate analysis was used, the data was presented in the form of distribution and frequency tables.The results show that the risk of decubitus events is mostly low risk as many as 34 respondents (43%) and a small proportion of high risk as many as 17 respondents (21%) from 80 respondents. The risk of occurrence of phlebitis is found in the majority of the early stages of phlebitis as many as 48 respondents (60%) and in the minority there are no signs of phlebitis as many as 32 respondents (40%). Aseptic measures in carrying out medical and non-medical actions in hospitals need to be improved and for further research it is hoped that length of stay, body weight can be used as research variables in observing the occurrence of decubitus and phlebitis in hospitals.